First-year Secondary Students' Perceptions of the Impact of iPad Use on Their Learning in a BYOD Secondary International School - Martin Watts; Ioannis Andreadis (Flexible Learning Association of New Zealand, 2023)
This study uses a statistical survey over three consecutive years to show how the first-year students of a mid-sized Bring Your Own Device (BYOD) secondary international school perceive the impact of using their own iPad on their learning. The students' perceptions show awareness of the usefulness and challenges associated with using their iPads in school life as well as at home. The students indicate several perceived benefits relating to having instant access to a variety of learning opportunities via the internet. However, they also indicate the challenges of keeping a balanced approach and avoiding overuse of their iPads inside and outside school (e.g., for gaming and social media). The original rationale for implementing the BYOD scheme did not anticipate specific benefits for students' academic outcomes (grades). However, academic performance has continued to be monitored to identify any adverse effects associated with the scheme. Students' overall academic performance has not been adversely affected since the scheme was implemented.